(untitled) (Eurasian Journal of Ecology, 2024)
According to the State Inspectorate for environmental and technical Safety under the Government of the Kyrgyz Republic, the republic has 145 facilities for the treatment of domestic and industrial wastewater, 22 municipal treatment facilities, mechanical and biological treatment of wastewater from enterprises and organizations to which the population is connected. The discharge of wastewater after passing through treatment facilities is carried out into the environment. Of the 145 wastewater treatment plants: 14 are discharged into surface water bodies, 5 into dry streams and rivers, 2 onto terrain, 114 into irrigation and SDS [http: //data.movegreen. kg/indicator/49]. Pollution of water bodies is no less dangerous than their depletion, and the deterioration of the sanitary and environmental situation, together with the growth of wastewater, reduces the quality of water resources, as evidenced by the environmental insecurity of the population, which is closely related to the nature of the use of water resources. Wastewater bioremediation using algae and bacteria represent a significant potential for sustainable pollutant reduction, as well as contributing to resource recovery and valorisation of microalgae biomass and is known as a promising approach to water treatment and the Ak-Buura River. The use of consortia of microalgae and bacteria can provide several advantages over the use of microalgae monocultures alone for bioremediation treatment of various wastewaters, such as improved removal of nutrients or antibiotics and reduced risk of pollution. Key words: transboundary rivers, environmental safety phytobenthos phytoplankton, environmental safety, runoff, eutrophy.